Challenging Conceptions of Diversity and the Good Life in Plato's Republic. - Talbert, B.
Challenging students? intuitions and unexamined beliefs, and drawing out the logical consequences of those beliefs has long been the teaching methodology of philosophers. These same educational goals are crucial to Plato?s philosophy of education, which is illustrated through Socrates? metaphor of the midwife?the teacher helps the students create something novel out of that which they already have in them: in other words, it challenges them to rethink their assumptions. This paper will consider some of the ways in which Plato presents the reader with opportunities to see the examined life as a series of rethinkings about what it means to live a good life with other people who are different from one?s self. The rethinkings that Plato?s dialogues prompt speak to some of the most prevalent assumptions that students typically and unquestioningly believe about diversity and the good life.
Keywords: Philosophy -- Periodicals; Teaching -- Periodicals